Arylmercapto substituted tetraazaperopyrene derivatives and their oxidation to tetrasulfones: photophysics and electrochemistry - Langbein, Susanne; Wadepohl, Hubert; Gade, Lutz H. (The journal of organic chemistry, 2015)
Fourfold arylmercapto substituted tetraazaperopyrene (TAPP) derivatives were obtained by direct nucleophilic substitution of the tetrabrominated TAPP or via Cu-catalyzed S-C coupling. These new materials display a characteristic bathochromic shift of their visible absorption and emission bands by ca. 200 nm compared to the unsubstituted parent compound. Two of the sulfide derivatives were oxidized with periodate to give their corresponding sulfones.